Bangladesh : Poverty Reduction Strategy Paper. - International Monetary Fund. African Dept. (Washington, D.C. : International Monetary Fund, 2012)
Poverty Reduction Strategy Papers are prepared by member countries in broad consultation with stakeholders and development partners, including the staffs of the World Bank and the IMF. Updated with annual progress reports, they describe the countries macroeconomic, structural, and social policies in support of growth and poverty reduction, as well as associated external financing needs and major sources of financing. This country document for Bangladesh is being available on the IMF website by agreement of the member country as a service to users of the IMF website.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet